Analysis of Constraints in Implementing Inaportnet at Sorong Port Class 1 - Arief Nashrul Firdani; Heri Supomo (International Journal of Offshore and Coastal Engineering, 2024)
This research examines the challenges that arise when expanded logistics operations are conducted utilizing the Inaportnet program, which has been in place at KSOP Class 1 in Sorong City since 2017. This study examined a population using the inaportnet application at the Port of Sorong City. Using a qualitative descriptive methodology, The inaportnet application, which is currently being improved, users or stakeholders who need guidance with how to use the application, and the occasionally in-interfered-with signal in the Port of Sorong City are a few challenges that must be overcome. It is hoped that the findings of this analysis and discussion will provide information and recommendations for implementing Inaportnet at the Port of Sorong City to ensure service fairness (first come, first served), realize transparency of ship and goods services at the Port, hasten the completion of ship and goods services, and reduce costs associated with handling ship and goods services.